The Impact of School Programs, Teacher Quality, and Location on Parental Decision-Making in School Selection - Debi Ayu Sri Maharani Tanjung; Moh. Bukhori; Tin Agustina Karnawati (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of flagship programs, school location, and teacher quality on parents' decisions in choosing a school. A quantitative approach with a survey method was employed, using a population of 73 parents of students in grades 1 to 6. Total sampling was used, and data were analyzed through multiple linear regression with SPSS version 27. The results indicate that flagship programs, school location, and teacher quality each have a positive influence on parents' school selection decisions. These findings suggest that schools should continually evaluate and improve educational quality, particularly regarding flagship programs, student safety, and the overall learning environment.